Facing Global Dynamics with Effective Strategy: A Tasted Organizational Change Management Approach - Ronal Aprianto; Chandra Lukita; Asep Sutarman; Richard Andre Sunarjo; Rifqa Nabila Muti; Ellen Dolan (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2025)
In an era of rapid globalization and digital transformation, organizations must adopt adaptive strategies to navigate complex market shifts. This study explores a tested Organizational Change Management (OCM) approach to enhance business resilience and sustainability. Using a quantitative research methodology, we conducted a structured survey involving 200 business executives across various industries to analyze the effectiveness of strategic OCM models. The results indicate that organizations implementing structured OCM frameworks experience a 35% increase in operational efficiency, a 28% improvement in employee adaptability, and a 40% reduction in resistance to change. Our study introduces a novel hybrid model, integrating Kotters Change Model with Agile methodologies, ensuring a balance between structured change and adaptive flexlibility. The findings contribute to existing literature by demonstrating how real time data driven decision making enhances the success rate of organizational transformations. This research provides valuable insights for business leaders and policymakers in aligning corporate strategies with global market dynamics, fostering innovation, and maintaining competitive advantages.